Qualitative and quantitative evaluation of acute angle-closure mechanisms - Yanin Suwan (2018)
© 2017 The Author(s). Background: To evaluate ocular biometric parameters in different subtypes of acute angle closure and compared to fellow eyes of AAC and PACS eyes. Methods: This is a retrospective chart review study. A total of 167 eyes (96 patients) consisting of 71 AAC eyes, 71 fellow eyes of AAC, and 25 PACS eyes were recruited. All patients underwent ocular examination and biometry. The mechanism of AAC was confirmed by ultrasound biomicroscopy. We then subdivided AAC eyes into four subgroups: crowded-angle (CR), lens subluxation (LS) pupillary block (PB), and plateau iris syndrome (PL). Outcome variables included anterior chamber depth (ACD), lens thickness (LT), vitreal length (VL), axial length (AL), lens position and relative lens position (LP and RLP, respectively), and lens axial length factor (LAF). Results: Among the three groups, ACD was shallower in AAC eyes than fellow eyes of AAC and PACS eyes (p < 0.01 for both) and AAC eyes demonstrated a lesser LP and RLP. The LT, VL, AL, and LAF were not significantly different among the three groups. Among the four subgroups, LS displayed the most shallow ACD (p = 0.01). The lens position in PL was greater than in CR and LS (p < 0.05 and <0.01, respectively). Conclusions: AAC eyes had a more anterior lens position than fellow eyes and PACS eyes, though lens thickness did not differ among the groups. As such, an anterior lens position may offer more sensitive prognostication regarding future development of AAC compared to lens thickness.